Molecular phylogenetics and molecular clock dating of Sapindales based on plastid rbcL, atpB and trnL-trnF DNA sequences. Issue 5 (12th October 2016) - Muellner-Riehl, Alexandra N.; Weeks, Andrea; Clayton, Joshua W.; Buerki, Sven; Nauheimer, Lars; Chiang, Yu-Chung; Cody, Sarah; Pell, Susan K.
Abstract: This study focuses on reconstructing the time‐calibrated phylogeny of the nine families comprising the order Sapindales, representing a diverse and economically important group of eudicots including citrus, mahogany, tree‐of‐heaven, cashew, mango, pistachio, frankincense, myrrh, lychee, rambutan, maple, and buckeye. We sampled three molecular markers, plastid genes rbcL and atpB, and the trnL‐trnLF spacer region, and covered one‐third of the generic diversity of Sapindales. All three markers produced congruent phylogenies using maximum likelihood and Bayesian methods for a set of taxa that included outgroups, i.e., members of the closely related orders Brassicales and Malvales, and the more distantly related Crossosomatales, Ranunculales, and Ceratophyllales. All results confirmed the current delimitation of the families within Sapindales, and the monophyly of the order. Concerning inter‐familial relationships, Biebersteiniaceae and Nitrariaceae formed a basal grade (or sister clade) to the rest of Sapindales with moderate support. The sister relationship of Kirkiaceae to Anacardiaceae and Burseraceae was strongly supported. The clade combining Anacardiaceae and Burseraceae as well as the clade combining Meliaceae, Simaroubaceae, and Rutaceae each received strong support. The sister relationship between Meliaceae and Simaroubaceae was moderately supported. The position of Sapindaceae could not be resolved with confidence. The Sapindales separated from their sister clade, comprising Brassicales and Malvales, in the Early Cretaceous at ca. 112 Ma, and diversified into the nine families from ca. 105 Ma until ca. 87 Ma during Early to Late Cretaceous times. Biebersteiniaceae and Nitrariaceae have the longest stem lineages observed in Sapindales, possibly indicating that extinction may have had a greater role in shaping their extant diversity than elsewhere within the order. Divergence within the larger families (Anacardiaceae, Burseraceae, Meliaceae, Rutaceae, Sapindaceae, Simaroubaceae) started during the Late Cretaceous, extending into the Paleogene and Neogene.